The Book of the Elders : Sayings of the Desert Fathers: The Systematic Collection - Wortley, John (Book collections on Project MUSE., 2012)
"The sayings and stories (or apophthegmata) of the early desert fathers began to be written down, collected, and codified by the fifth century. The earliest attempts to codify them are now lost. As the collection grew, they were first organized alphabetically, according to the name of the abba who spoke them, in a major collection known as the Apophthegmata Patrum Alphabetica. A supplementary collection, the Anonymous Apophthegmata, followed. Later, both collections were combined and arranged systematically rather than alphabetically. This collection was created sometime between 500 and 575 and later went through a couple of major revisions, the second of which appeared sometime before 970. The second revision was published in an excellent new critical edition, with a French translation, in 1993. Now, in The Book of the Elders, John Wortley offers an Enlgish translation of this collection, based entirely on the Greek of that text."--Jacket.